STRATEGI PEMBELAJARAN NAHWU SARAF DI MA PONDOK PESANTREN - Ma’rifatun . (STAINU Purworejo, 2019)
Naḥwu ṣaraf is a very important science to support and facilitate in mastering Arabic. Because of the importance of these two sciences, they are known as tools, which are tools for reading yellow/classical books. The aim of naḥwu ṣaraf learning as a tool for reading the texts of the book is a tool or key to understanding the contents of Arabic texts, especially those related to Islamic religious knowledge. But until now many students of Islamic boarding schools based on pesantren find it difficult to understand the science of naḥwu ṣaraf. Departing from these problems, the authors intend to examine the naḥwu ṣaraf learning strategy applied by Madrasa Aliyah Ali Maksum teachers in the Krapyak Islamic Boarding School in Yogyakarta and Al-Imdad Featured Islamic Schools in Al-Imdad Islamic Boarding School in Bantul. This research is qualitative research. The method of data collection is done by the method of observation, interviews, and documentation. Furthermore, the method used to analyze data is descriptive-analytic, which is the method used to compile data that has been collected, explained, and then analyzed. The results of this study are; naḥwu ṣaraf learning strategies undertaken by Madrasah Aliyah Ali Maksum and Madrasah Aliyah Featured Al-Imdad teachers include the following: strategies for reading the text of the book, muḥādathah Arabic, game strategies (language games/demonstrations), development of naḥwu ṣarafs that suit your needs or those that are in need most widely used, giving gifts/sanctions, motivating students with kalam wisdom or bait na'am (shi'ir), application examples in the form of al-Qur'ān and al-Hadīth. This learning strategy emphasizes naḥwu ṣaraf learning strategy innovation so that students are able to read books or texts that suit their needs. This has achieved significant results because it has reached the set value (KKM). Even Madrasah Aliyah Ali Maksum students often win in various yellow book reading competition (MQK) events, both at the district, provincial, and even national level.